An investigation into increased productivity of small scale anaerobic digesters by means of temperature management - Carolissen, Sanchez (Energy Research Centre, 2018)
The use of biological waste as a primary energy source for the production of biogas, by the process of anaerobic digestion, has been commonly used in the past by small communities and on a larger scale by waste water treatment plants. In the latter, the biogas is traditionally used for heating of the digesters in order to increase process performance. Smaller scale anaerobic digesters using food waste as a primary energy source for biogas production could be implemented for residences and restaurants. The biogas produced could be used for cooking and heating purposes. Whilst common designs for such smaller digesters do not provide for heating, there may be warm waste water on site to elevate the operating temperature and thus improve gas yield. This dissertation reports an experiment aimed at improving the performance of an existing anaerobic digester located at the Leo Marquard Hall (LMH) residence of the University of Cape Town. The 6 m³ digester has been operated using food waste as its sole substrate. The volume of gas produced is unknown as there are no gas measurement devices on site. In the past it has been roughly estimated from pressure readings before and after gas use. The digester operates at ambient temperature which averages 16 °C over the year, which is suboptimal. The anaerobic digester is not equipped with a temperature measurement device to monitor operating temperature. Two hypotheses were formulated and tested. The first stated that the temperature profile of the waste water leaving the LMH residence will have peaks in the morning and evening periods when the majority of students shower. The peak temperature periods will be in the morning before breakfast and in the evening after dinner. The temperature during these times is expected to be above 30 °C. In order to test the first hypothesis, a thermocouple with temperature data logger was installed to record the temperature of waste water in the manhole drain leaving the LMH residence. The temperature data recordings confirmed the temperature peak of waste water leaving LMH residence at an average temperature of 30.5 °C in the morning. However, a clear evening temperature peak was not identified. Thus the hypothesis was only true for the morning temperature peak of waste water leaving LMH residence for weekdays when lectures take place. The second hypothesis stated that, adding a portion of the 30 °C waste water into the LMH anaerobic digester will result in the digester running at 5 °C above the normal average operating temperature, and thus increase the productivity of the anaerobic digester. In order to test the second hypothesis the design and installation of a pumped pipe system was completed in order to pump waste water from the LMH residence waste water outlet manhole gravity sewer to the LMH anaerobic digester. By loading the LMH anaerobic digester with 600 ℓ of warm waste water, the maximum digester temperature increase obtained was 5 °C relative to the normal cold water operation. The maximum increases in total weekly biogas and methane production achieved were 238 % and 260 % respectively, relative to the average weekly cold water operation. The operating temperature of small scale anaerobic digesters is a very important factor for the performance of the anaerobic digester. This research shows that increasing the operating temperature of a small scale anaerobic digester by as little as 5 °C could double the performance of the anaerobic digester. The site location for the installation of small scale anaerobic digesters should be investigated at design stage by taking into consideration the operating temperature. The digester could be installed in close proximity to both an organic waste stream and warm waste water stream that could affect the feasibility of a particular project installation.